2018
DOI: 10.1074/jbc.ra118.004542
|View full text |Cite
|
Sign up to set email alerts
|

A functional study of all 40 Caenorhabditis elegans insulin-like peptides

Abstract: The human genome encodes 10 insulin-like genes, whereas the genome remarkably encodes 40 insulin-like genes. Knockout strategies to determine the roles of all the insulin/insulin-like peptide ligands (INS) in has been challenging due to functional redundancy. Here, we individually overexpressed each of the 40 genes pan-neuronally, and monitored multiple phenotypes including: L1 arrest life span, neuroblast divisions under L1 arrest, dauer formation, and fat accumulation, as readouts to characterize the functio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
66
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 77 publications
(76 citation statements)
references
References 50 publications
5
66
1
Order By: Relevance
“…The influence of each of the 40 ILPs on developmental rate has not been measured. Overexpression of several ILPs can promote precocious cell division during starvation . However, analysis of a subset of ins gene mutants did not identify any mutants in which M cell lineage divisions were delayed and even compound mutants of ins‐4 , ins‐5 , ins‐6, ins‐7 , and daf‐28 , ILPs that prevent dauer formation, fail to delay these divisions .…”
Section: Elegans Respond To Nutrient Limitation By Altering Behavimentioning
confidence: 98%
See 4 more Smart Citations
“…The influence of each of the 40 ILPs on developmental rate has not been measured. Overexpression of several ILPs can promote precocious cell division during starvation . However, analysis of a subset of ins gene mutants did not identify any mutants in which M cell lineage divisions were delayed and even compound mutants of ins‐4 , ins‐5 , ins‐6, ins‐7 , and daf‐28 , ILPs that prevent dauer formation, fail to delay these divisions .…”
Section: Elegans Respond To Nutrient Limitation By Altering Behavimentioning
confidence: 98%
“…Additional ILPs likely contribute to the dauer decision, as loss of many individual ILPs enhance dauer formation in sensitized genetic backgrounds or under sensitizing conditions ( Table 1 ). Based on the ability of mutants to suppress dauer formation in at least one sensitized background, several ILPs were proposed to act as antagonists, Recently, however, overexpression of ILPs using a pan‐neuronal promoter demonstrated that several ILPs could enhance one insulin‐dependent phenotype, while suppressing another, suggesting that context may also be important in determining whether ILPs act as agonists or antagonists (Table ) …”
Section: Elegans Respond To Nutrient Limitation By Altering Behavimentioning
confidence: 99%
See 3 more Smart Citations